Assessment of Transformed Properties In Vitro and of Tumorigenicity In Vivo in Primary Keratinocytes Cultured for Epidermal Sheet Transplantation - A. Thépot; A. Desanlis; E. Venet; L. Thivillier; V. Justin; A. P. Morel; F. DeFraipont; M. Till; V. Krutovskikh; M. Tommasino; O. Damour; P. Hainaut (Journal of Skin Cancer)
Epidermal keratinocytes are used as a cell source for autologous and allogenic cell transplant therapy for skin burns. The question addressed here is to determine whether the culture process may induce cellular, molecular, or genetic alterations that might increase the risk of cellular transformation. Keratinocytes from four different human donors were investigated for molecular and cellular parameters indicative of transformation status, including (i) karyotype, (ii) telomere length, (iii) proliferation rate, (iv) epithelial-mesenchymal transition, (v) anchorage-independent growth potential, and (vi) tumorigenicity in nude mice. Results show that, despite increased cell survival in one keratinocyte strain, none of the cultures displayed characteristics of cell transformations, implying that the culture protocol does not generate artefacts leading to the selection of transformed cells. We conclude that the current protocol does not result in an increased risk of tumorigenicity of transplanted cells.